The intellectual transformation of modern design discourses in the Eastern Mediterranean Region (EMR) - Saad, Qassim (Phyllis M. Taylor Center for Social Innovation and Design Thinking at Tulane University and the DRS Pluriversal Design Special Interest Group, 2020)
This study will offer an overview of applied discourses of design in the Eastern Mediterranean Region (EMR), including Egypt, Palestine, Lebanon, Syria, Jordan, and Iraq. Since the 1940s, these countries have been known for their pioneering statues, creative engagements, and influence on shaping, resourcing, and sustaining the emergent project of modernity in the EMR. Studies of these countries’ contemporary design discourses are underdeveloped, with extremely limited studies addressing their context and practices. This study will survey identical phases throughout the contemporary history of these countries, exploring and critically reviewing key themes in their regional sociopolitical rhetoric since the 1950s. The study demonstrates the need to utilise design discourses to empower regional societies currently facing unrest. The study identified four thematic periods reflecting the influence of regional sociopolitical rhetoric: (1) the colonisation era, articulating a sociocultural perspective concerning craftmaking and craftsmanship; (2) postcolonisation and the emergence of modernity, with design emerging as a cultural manifestation that enhances regional socioeconomic development; (3) the rise of the national state, with design as a sociopolitical manifestation utilised to reinforcing identity and local traditions; (4) expansion of autocracy and current discord, with the emergence of social design. These thematic periods are explored through selected examples from across the EMR.